The Effect of Mango (Mangifera indica L.) Juice on Paracetamol â Induced Liver Cell Damage in Mice (Mus musculus) - Ras, Samiaji Abbas; Listyaningsih, Endang; Sari, Yulia (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Mango (Mangifera indica L.) contains beta-carotene and vitamin C which were thought to protect the liver from free radicals. In present study, Mango (Mangifera indica L.) juice with certain dose was evaluated for its protective effect on paracetamol induced liver damage in mice. Methods: This study used 28 male Swiss Webster mice were equally divided into four groups. Animals of Control Group (KK) were given aquadest and Treatment Group I (KP1) received paracetamol for 3 days. Treatment Group II and III (KP2 and KP3) not only received paracetamol, but also received multilevel doses of Mango (Mangifera indica L.) juice (0,2 mg and 0,4 mg) for 14 days. Mice were sacrificed on the 15th day and histological preparation was made to evaluate histological damage on liver. Liver histological featuresÂ wereÂ assessedÂ byÂ countingÂ theÂ numberÂ of hepatocyte on centrolobuler zone undergoing pyknosis, karyorhexis, and karyolysis. Data were analyzed using theÂ One Way ANOVA test (Î± = 0.05) and the Post Hoc Multiple Comparisons (LSD) test (Î± = 0.05). Results: The mean liver histological damage score was significantly higher on group of KP1= 61,8Â±7.991, while group ofÂ KK= 26,21Â±4.828 as the least. KP3 group had fewer numbers of liver histological damage (40,09Â±7.635) compared to the KP2 group (37,81Â±5.653). The results of One Way ANOVA test showed significant difference between the five groups (p = 0.000) and the results of LSD test showed significant differences between each other group (p < 0.005). Conclusion: Mango (Mangifera indica L.) juice showed protective effect against the hepatotoxicity induced by paracetamol in mice. Mango (Mangifera indica L.) juice with the dose of 0,4 mg/20 g body weight of mice showed a higher hepatoprotective effect than the dose of 0,2 mg/20 g body weight of mice. Keywords: Mango juice, paracetamol, histologic liver damage. Â